From disabled people's right to work to the duty to work? Changes in Swiss disability policy and its implementation at the cantonal level - Natalie Benelli; Antonin Zurbuchen; Morgane Kuehni; Peter Streckeisen; Spartaco Greppi (Social Work and Society, 2023)
The article discusses the current shift in Switzerland's disability policy from the right to work (in a sheltered workshop) for disability pensioners to the duty to work in the labour market for people with disabilities, whether they have a disability pension or not. The analysis of Swiss disability legislation and its implementation in the cantons of Basel-City, Ticino and Vaud shows that federal and cantonal disability policy questions the social and economic rights attached to a disability pension, in particular the right to be freed of the obligation to participate in the labour market, the right to be freed of the obligation to participate in welfare-to-work programmes in exchange for disability benefits, the right to work in a sheltered workshop and the right to supplementary benefits. These rights are being replaced by the (moral) duty for people with disabilities to integrate the labour market, with little chance of successful integration.